Psychological characteristics and entrepreneurial intention among Polytechnic students in Malaysia: A theory of planned behavior approach - Mokhtar, Rozita; Othman, Ahmad; Zainuddin, Yuserrie (ASEAN Universities Consortium of Entrepreneurship Education (AUCEE), 2010)
The onset of global economic downturn has slightlv affected the employment situation for the Malaysian Polytechnic's graduates reported by POLISAS Annual Report in 2004 (POLISAS, 2004: 32). The trend of working status for Malaysian Polytechnic Graduates from the year 2003 to 2006 where the rate of the employed, for Malaysian Polytechnic graduates tend to decrease over these periods but the rate of the unemployed graduates show a trend in an increasing. The increasing unemployment rate among the Polytechnic Graduates in Malaysia is a worrying trend. For many years, the issue cropped up again and again, made the news headlines, and even hit the parliament. This may sound painful for graduates but let's face it (MoHE, 2004: 2005; 2006; 2007). The Government recognizes the importance of self-einployment in employment creation. The attitude of current graduates who are seen to be too dependent on the government and private sectors for employment must be change. The inculcation of entrepreneurship values and changing the mindset as to view self-employment as a viable alternative to salaried employment has been intensified including in institutions of higher education. According to Amanat Tahun 2009 by the Minister of Higher Education, Dato' Seri Mohamed Khaled Nordin, about training, internship and entrepreneurship programmes must be encouraged to the Malaysian Universiy Students. Basic Entrepreneurship Culture Module should be done by HEIs (IPTA) to apply high moral value and changing in mindset for graduates to become self-reliant by having entrepreneurship spirit and culture. As such, efforts have been intensified to create more business opportunities for self-employment among the graduates. Furthermore, with this skill can create working opportunities to others (MoHE, 2009). Therefore, this conceptual paper proposed the intention to be entrepreneur can be explained by Ajzen 's (1985) Theory of Planned Behavior. Psychological characteristics will effect of attitudes, subjective norms, perceived behavioral control and self-eficacy. Consequently, the study predicted the entrepreneurial intention of the Malaysian Polytechnic students.